Cost Accounting Based on Activities as a Tool to Determine the Cost of Banking Services (Case study of Rasheed Bank branch of the Doraa) - Ahmed M. Hussein; Ali H. N. Bni lam (Journal of Madenat Alelem University College, 2020)
The research aimed at clarifying the role of cost accounting in banking and providing competitive advantage through the pricing of banking services and shedding light on the necessary data to calculate the cost of banking services. The research adopted a descriptive approach to prove its hypothesis. This led to the calculation of the cost of service accurately. The sample of the research was The Rasheed Bank branch of the Doraa. The research concluded that although there are good financial accounting document and records information that represents the inputs of the cost system, as it is found that there are no accurate details of the expenses and revenues in the accounting records. Therefore the following recommendation was drawn that the cost accounting system should be applied based on (ABC) activities in the bank to accurately determine the cost of banking service and to keep pace with developments in the competitive environment.